Possible Immunotherapeutic Strategies Based on Carcinogen-Dependent Subgroup Classification for Oral Cancer - Sun, Jiwei; Tang, Qingming; Zhang, Junyuan; Chen, Guangjin; Peng, Jinfeng; Chen, Lili (Frontiers in Molecular Biosciences, 2021)
Oral cavity serves as an open local organ of human body, exposed to multiple external factors from the outside environment. Coincidentally, initiation and development of oral cancer are attributed to many external factors, such as smoking and drinking, to a great extent. This phenomenon was partly explained by the genetic abnormalities induced by carcinogens traditionally. However, more and more attention has been attracted to the influence of carcinogens on local immune status. On the other hand, immune heterogeneity of cancer patients is a huge obstacle for enhancing clinical efficacy of tumor immunotherapy. Thus, in this review, we try to summarize the current opinions about variant genetic changes as well as multiple immune alterations induced by different oral cancer carcinogens, and discuss the prospects about targeted immunotherapeutic strategies based on specific immune abnormalities caused by different carcinogens, as a predictive way to improve clinical outcomes of immunotherapy-treated oral cancer patients.